Between Excess and Subtraction: Scenographic Violence in Howard Barker’s Found in the Ground - Lara Maleen Kipp (Sillages Critiques)
The article examines the violence produced by the scenography of Howard Barker's Found in the Ground, which emerges out of the play’s formal experimentation. Thematically, the play is rife with violence, such as former Nuremberg judge Toonelhuis’ consumption of the remains of high-ranking Nazis he sentenced to death, the continuous burning of books and the retelling of various murders by the war criminal Knox. Found in the Ground re-visions the collective European memory of the Holocaust; this thematic violence is expanded and subverted by scenographic means, radically reimagining the historical context. The particularity of the spatio-temporal, audio-visual rendering of violence in Barker’s text is the focus of this article. The article relates the play to Artaud’s conception of cruelty and to Lyotard’s thinking on the sublime. It contextualises the play through Barker’s theoretical writings, Lingis’ notion of catastrophic time (2000) and Aronson’s proposition of the stage as an abyss (2005).